COVID-19 pandemic: mental health (distress as depression) in orthodontists - Eloisa Peixoto Soares Ueno; Liana Fattori; Edgard Michel-Crosato; Wilze Laura Bruscato; José Rino Neto; João Batista de Paiva (Clinical and Investigative Orthodontics)
Objectives For health professionals, pandemic conditions impacted all societal aspects, including economic, wellness, and mental health. This study analysed sociodemographic factors, post-traumatic stress disorder symptoms (PTSD), and depression levels caused by the coronavirus disease 2019 (COVID-19) pandemic in orthodontists.Materials and Methods A sociodemographic questionnaire, the Impact of Event Scale (IES), and the Patient Health Questionnaire (PHQ-9) were used. Following data collection, multiple statistical analyses were applied: scores were compared using the Mann-Whitney and Kruskal-Wallis tests, followed by Dunnett's multiple comparisons. The association between variables was verified using Chi-square or likelihood ratio tests. Multiple logistic regression models were estimated after bivariate logistic regression tests (p < 0.10). The final models using the Stepwise backward selection method were assessed for variables at 5%.Results Of the respondents, 69.3% were women, and their mental health questionnaire scores were significantly higher (p < 0.001). The IES avoidance and PHQ-9 scores were statistically different between the age groups (p = 0.040 and p < 0.001, respectively). Subjective distress was associated with years of practice, monthly income, fear of contracting COVID-19 during dental care, transmitting COVID-19 to patients, and thinking about the future (p < 0.05). Depression was significantly associated with orthodontic practice type, self-confidence in providing dental care, pandemic impact on dental practice, remote care, monthly income, changes in financial expenses, fear of contracting COVID-19 and thinking about the future (p < 0.05).Conclusion Over half of the orthodontists experienced moderate-to-severe mental distress, and the same number suffered from mild-to-severe depression during the pandemic.